The importance of design as a creative process in business schools: How to fill the design/business knowledge and communication gap? - Almeida, I. de. (Proceedings of the 13th World Congress of the RSAI. Smart regions - Opportunities for sustainable development in the digital era, 2021)
In most Business Schools (BS), Design in business education plays a minimal role. It is neither part of the core basic learning courses nor part of the electives. No courses in design, corporate identity, graphic design, communication design, environmental design, or product design were found in this study. When business students are enrolled in design principles, they learn it loosely, as part of new product development or entrepreneurship classes. Business teachers simply assume that when corporate design decision-making is needed, the managers will simply ask a designer. However, designers are not educated in business and business managers are not educated in design. Without design in the curriculum, BS is far away from the real business world. Therefore, why BS does not change the curriculum to meet the real business-world needs? The current study addresses the (i) perceptions of business education and training experts; (ii) accreditation and curriculum requirements; and (iii) scientific journal articles, books on current standards and processes in business education. The curriculum specifications for business programs are generally established by the International Association for Management Education (AACSB). Our results reveal that the AACSB demanding: the business curriculum should include "accounting, economics, mathematics, statistics and behavioural science" alongside "basic written and oral communication skills and quantitative analysis". No mention of design or quality analysis is done. Moreover, the specific content of the course does not matter for the accreditation process. Instead, the business programs evaluation is performed following their goals. Design and design management were not mentioned when comparing goals and curricula from several Portuguese business schools. In our research, when business teachers were questioned about the hypothesis of curriculum changing, one of the most cited answers was that “Someone should have a vision. If there is no leader, nothing will happen" However, to develop non-traditional curricula, it requires efforts from all, and several faculty members, particularly the teachers, are overstretched. Likewise, it is much easier to teach the same subject multiple times. We conclude that the teacher’s passion for design must be sufficiently robust to drive change. But, in another hand, the business students must demonstrate curiosity and willingness to engage. When a new course is introduced in a traditional curriculum it will be appreciated, and the first criterion is the extent of demand for it. An average of 30 students must enrol. The second is concerning the professor and the new course must be well taught. If both conditions are met, they can continue. But the new and real-world-touching courses are always introduced as electives, and students put a lower priority on electives than on core needs – the compulsory courses. As a result, what needs to be done to overcome the curriculum stalemate, the priority of the students, and the burnout of the faculty members? What could cause business schools to change? What would make possible the inclusion of design in Business curricula, despite the above-mentioned obstacles? The present work is a search for adequate answers.